Hydration of acetic acid-dimethylamine complex and its atmospheric implications. (15th December 2019) - Li, Jie; Feng, Ya-Juan; Jiang, Shuai; Wang, Chun-Yu; Han, Ya-Juan; Xu, Cai-Xin; Wen, Hui; Huang, Teng; Liu, Yi-Rong; Huang, Wei
Abstract: Atmospheric aerosols are closely related to weather, climate and human health, and New particle formation (NPF) is a major source of atmospheric aerosols. Currently, some field observations and experiments indicate that acetic acid (HOAc) could be involved in NPF events. However, mechanism of acetic acid nucleation is still unclear. In this study, the low-lying structures and thermodynamics of acetic acid (HOAc)-dimethylamine (DMA)-water (W) system were studied at PW91PW91/6–311++G (3df, 3pd) level. We found that acetic acid forms relatively stable clusters with dimethylamine, and that proton transfer enhances the strength of the hydrogen bond in (HOAc) (DMA) (H2 O)n (n = 2–4) clusters. Temperature has an important effect on the distribution of isomers, especially for (HOAc) (DMA) (H2 O)2 clusters. Besides, all the isomers contribute to the nucleation of clusters. The various RH has a negligible effect on the hydrate distribution. However, the non-hydrated clusters are always dominant and they are easy to form stable cluster, as seen from the comparison of hydrate distributions and cluster formation rates. The above analyses indicate that (HOAc) (DMA) is relatively stable and some larger clusters based on (HOAc) (DMA) may participate in new particle formation. Highlights: Clusters consisting of HOAc, DMA and H2O are relatively stable. Water molecules make the hydrogen bond in HOAc-DMA stronger. High RH could promote the HOAc-DMA cluster growth. Hydration could decrease the evaporation rates of HOAc and DMA.